National Games are a Symbol of Our Values - Tokhirovna, Ismoilova Hurshida (European Journal of Life Safety and Stability (2660-9630), 2021)
The article covers the scientific study of increasing social activity through National Games in neighborhoods, increasing their activity and the content of development of National Games among them. The results of the research conducted in this article, the analysis of playing games on mobile phone in parts of the regions, the problems of promoting the development of National Games are described.